SISTEM LAYANAN SIRKULASI PEMINJAMAN PADA PERPUSTAKAAN SMA NEGERI 1 JUNTINYUAT KABUPATEN INDRAMAYU - Nanda Yudisman, Septevan; Kusrinih, Sri (UIN Imam Bonjol Padang, 2024)
This research was conducted at the Library of SMA Negeri 1 Juntinyuat, Indramayu Regency. This research aims to determine the loan circulation service system usedin the SMA Negeri 1 Juntinyuat Library, Indramayu Regency. This research uses a descriptive qualitative research method, namely by taking research data from the field directly. Data collection techniques were carried out using observation, interviews, and documentation in the Juntinyuat 1 Public High School Library. Circulation service activities at the SMA Negeri 1 Juntinyuat Library, Indramayu Regency, are first: membership services, second: loan and return services for library materials, and third: providing sanctions to librarymembers who violate the rules. The obstacles faced are that there are still many students who are not used to using computers and there are differences in the characteristics and attitudes of the students so the use of the circulation service system in the Juntinyuat 1 Public High School Library is still not working optimally because they are not used to using the SLiMS9 (Bulian) application on computers.